Operating performance of Malaysian initial public offerings - Tapa, Afiruddin; Mazlan, Ahmad Rizal (2013)
This paper examines the operating performance of Malaysian Initial Public Offerings. Overall, we find that the operating performance declines after being listed in stock market. The listing causes a decline in profitability, sales growth and efficiency, and shows significant increase for leverage and sales volume. We then explore the relationship between IPOs’ underpricing and post-issue operating performance and find the underpricing is insignificant in explaining the post-issue operating performance. Using a crosssectional analysis, we examine the relation between post-issue performance and the long-run market returns of Malaysian IPOs. The results show that investors evaluate the fundamentals of the firms by studying the accounting measures when they make their investment decisions.